Development of microprocessor learning media using zilog z-80 for vocational school students of electronic engineering expert program - Nurul Fitri Fathia; Ivan Hanafi; Muhammad Rif'an (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This development research aims to develop microprocessor learning media using Zilog Z80. The Learning Media quality is based on the following aspects: (1) media feasibility according to subject matter experts and media experts; (2) effective based on students ability test by pre test and post-test. The developed cycles and procedures refer to the ADDIE model (analysis, design, development, implementation, and evaluation). This development research produces learning media as microprocessor kits training and e-Learning namely